Examining the Canada–China agri‐food trade relationship: Firms, trading partners, and trading volumes. (5th July 2018) - Xie, Chaoping; Gao, Jianfeng; Grant, Jason H.; Anders, Sven
Abstract: The "new‐new" trade theory has dramatically shifted the focus of international economics research to heterogeneous firms and the margins by which firms participate in international trade. However, few studies have examined the dynamics of agricultural trade at the firm level. This paper employs China Customs data comprising the universe of Chinese firm‐level agricultural import transactions over the period 2000–2009 and develops an empirical strategy to decompose the growth of Chinese agri‐food imports of its four major suppliers, Canada, the United States, Brazil, and Argentina. Our findings reveal that China's growth in agricultural imports is highly concentrated among a small group of firms, where the top 10% of Chinese agricultural importers account for nearly 90% of its agricultural imports. We also find evidence of a significant turn‐over of importers of agri‐food products. Over 40% of new firms entering China's agricultural import market during our sample exited after just 1.7 years. Finally, decomposing import growth patterns for Canada and its competing suppliers reveals significant differences in the intensive and extensive margins of trade that hold important implications for trade policies aimed at enhancing Canada's position as a major agri‐food supplier in the Chinese market.